A dual band dual antenna with read range enhancement for UHF RFID tags - Bhaskar S.; Singh A.K. (My University, 2025)
This article presents a novel dual antenna structure for dual ultra high frequency bands (f1 = 866 MHz and f2 = 915 MHz) for radio frequency identification tags. The proposed structure consists of two dual band antennas, one acting as a receiving antenna and the other as a backscattering antenna at both the frequency bands. The receiving antenna is designed to have input impedance complex conjugate to the impedance of tag IC in order to maximize power transfer between the antenna and the microchip. The backscattered antenna is designed to have real-valued input impedance at both the operating frequency bands to obtain maximum differential radar cross section leading to read range enhancement. The dual band receiving antenna is designed by embedding a pair of thin slits at a radiating edge of inset fed microstrip antenna. The backscattering antenna is comprised of two elements, one is a comb-shaped open ring element, and the other is a meander line structure which is within the open ring element. Compared to conventional antennas, the proposed dual antenna structure provides a read range enhancement due to improved maximum differential RCS. The proposed dual antenna produced 4.3 m and 6.8 m read range at 866 MHz and 915 MHz, respectively. © 2019 Wiley Periodicals, Inc.